Development and usability testing of diabetes risk calculator (diacal): a health education application - Febriani, Dita Hanna; Aryu, Scholastica Fina (SHM Publisher, 2024)
Despite the growing popularity of the mobile health application, the application that addressed to calculated diabetes risk is still limited. DiaCal was developed to prevent type 2 diabetes mellitus by screening and early detection approach. This study aimed to develop and examine the usability of DiaCal smartphone application-based education. This study was conducted with a cross-sectional approach. The framework of this application is based on the American Diabetes Association diabetes risk screening instrument. The development of the DiaCal was divided into three phases: preparation, design, and piloting. System Usability Testing (SUS) instruments used to examine the user-level acceptance of this application. DiaCal app developed in android platform core modules: a) data entry, b) conversion and calculation, c) output of the risk assessment, d) education. Twenty respondents were recruited in this study to evaluate DiaCal through SUS instrument. The average adjective range score is 85.25 which indicates that the DiaCal application is in the “excellent” category and the grade level scale is in “A+”. This study showed a significant usability and acceptability of DiaCal in terms of effectiveness, efficiency, and satisfaction.